Improving Arabic Language Skills by Integrating the Durusul Lugah Al-'Arabia and Silsilah Al-Azhar As-Syarif Textbooks for PPDU Malang Students - Uril Bahruddin; Fahrizal Winky Ghifari; Najib Ahmad Shofiyullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Arabic learning for foreign speakers is not the same as for native speakers. Therefore, innovation is needed, including integrating teaching materials. This study aims to uncover the integration model of Arabic textbooks by describing the forms, influencing factors, and implications that have arisen from the development of Arabic. This research approach is qualitative with the type of case study. Data mining is carried out using observation, interviews, and documentation. The data analysis method is discriminatory-qualitative. The results of this study show that (1) the form of textbook integration is carried out by combining two textbooks, selecting the appropriate theme, and evaluating separately (2) Supporting factors are competent teachers, dormitories, language coaching, and the use of Arabic. Meanwhile, the inhibiting factors are the diversity of students' abilities, dense activities, and lack of examples. Finally, (3) the impact caused is the realization of the environment, increasing abilities, and being able to make students happy to learn Arabic. Therefore, this study concludes that language learning innovation can be carried out by integrating textbooks from various relevant sources per the objectives.